2022
DOI: 10.3390/ijms23052690
|View full text |Cite
|
Sign up to set email alerts
|

Plant Secondary Metabolites as Defense Tools against Herbivores for Sustainable Crop Protection

Abstract: Plants have evolved several adaptive strategies through physiological changes in response to herbivore attacks. Plant secondary metabolites (PSMs) are synthesized to provide defensive functions and regulate defense signaling pathways to safeguard plants against herbivores. Herbivore injury initiates complex reactions which ultimately lead to synthesis and accumulation of PSMs. The biosynthesis of these metabolites is regulated by the interplay of signaling molecules comprising phytohormones. Plant volatile met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(128 citation statements)
references
References 186 publications
0
88
0
1
Order By: Relevance
“…The majority of plants produce a wide variety of secondary metabolites that are toxic to pathogens and herbivores [139]. Recent studies have shown that gut microorganisms can assist the host in degrading toxic secondary metabolites.…”
Section: Potential Mechanism Of Detoxificationby Lepidopteran Gut Bac...mentioning
confidence: 99%
“…The majority of plants produce a wide variety of secondary metabolites that are toxic to pathogens and herbivores [139]. Recent studies have shown that gut microorganisms can assist the host in degrading toxic secondary metabolites.…”
Section: Potential Mechanism Of Detoxificationby Lepidopteran Gut Bac...mentioning
confidence: 99%
“…Secondary metabolites, as the end products or by-products of plant metabolism, are important mediums for the co-evolution of phytophagous insects and their host plants [ 1 ]. At present, nearly 400,000 secondary metabolites are known to be synthesized by plants, and these can be mainly divided into phenols, terpenoids, and nitrogen-containing compounds [ 2 ]. Among these, some secondary metabolites exert adverse effects on insects, including antifeedant, repellent, or toxic effects [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites play the foremost role in defense mechanism toward pathogens, pests, and herbivores. Many plants microbiome especially endosymbionts regulate defense mechanisms through secreting various metabolites (Divekar et al, 2022 ). Secondary plant metabolites belonging to the family of steroids, alkaloids, phenolics, flavonoids, and terpenoids function in innate immunity and defense response signaling (Pang et al, 2021 ).…”
Section: Role Of Biofertilizers In Biotic Stress Managementmentioning
confidence: 99%